Strategi Komunikasi Pemasaran dalam Meningkatkan Pelanggan pada Akun Instagram @Adekdekorasi_Medan - Siregar, Fitrah Alfisyah; Azhar, Anang Anas; Rozi, Fakhrur (Medan Resource Center, 2023)
This study aims to determine the marketing communication strategies used by the Instagram account @adekdekorasi_medan to attract customers. It employs a qualitative descriptive research method and applies the marketing mix theory. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data presentation, and drawing conclusions. The results reveal that @adekdekorasi_medan employs various marketing communication strategies on Instagram, such as online promotion, endorsements, enhancing the visual presentation of the account, and offering promotions. These strategies help attract and retain potential customers. Despite the fierce competition in the social media decoration services industry, @adekdekorasi_medan has managed to maintain its presence since 2000